What artifice can and cannot tell us about animal behavior - Powell, Daniel L. (Curr Zool, 2017)
Artifice—the manipulation of social and environmental stimuli—is fundamental to research in animal behavior. State-of-the-art techniques have been developed to generate and present complex visual stimuli. These techniques have unique strengths and limitations. However, many of the issues with synthetic animation and virtual reality are common to playback experiments in general, including those using unmanipulated video or auditory stimuli. Playback experiments, in turn, fall into the broader category of experiments that artificially manipulate the array of stimuli experienced by a subject. We argue that the challenges of designing and interpreting experiments using virtual reality or synthetic animations are largely comparable to those of studies using older technologies or addressing other modalities, and that technology alone is unlikely to solve these challenges. We suggest that appropriate experimental designs are the key to validating behavioral responses to artificial stimuli and to interpreting all studies using artifice, including those that present complex visual displays.